Switchable filter compensating installation in AC traction network - L. A. German; A. S. Serebryakov; V. L. Osokin; D. V. Yakunin (Вестник Научно-исследовательского института железнодорожного транспорта, 2020)
In the AC traction network, the use of adjustable transverse capacitive compensation systems has become necessary primarily for normalizing the voltage at the current collector of the electric rolling stock. Currently, static reactive power generators are used at the sections of the traction network, which have proved their effectiveness in increasing and stabilizing the voltage level, as a result of which the railway capacity is increased. This article substantiates the necessity and expediency of the inclusion of adjustable transverse capacitive compensation installations at sectioning posts in AC traction networks to normalize the voltage at the current collector of electric rolling stock, and therefore, increase the throughput capacity of railway sections. It is shown that, in modern conditions, it is expedient and economically justified to modernize existing unregulated installations with transferring them to a controlled mode by introducing an additional subsequently connected second section of capacitors, which is automatically shunted by the switching device at high loads in the traction network. Modernized installation, proposed by the authors and called switchable, has been successfully operating on the Gorky Railway for more than 6 years. A description of the proposed installation is given and the results of a theoretical analysis of transients during shunting and unloading of the additional section are presented. An algorithm for switching the proposed installation is  given. It is shown that the additional section should be shunted at a time when the voltage across the capacitors is zero. Theoretical and experimental oscillograms of switching processes are presented. Recommendations are given for choosing thyristors for a controlled key, as well as recommendations for improving the reliability of the proposed installation.